Characterization of avian adenovirus FAdV-4/6/2009 isolate RABIES - O. S. Osipova; M. A. Volkova; N. G. Zinyakov; S. P. Lazareva; V. Yu. Sosipatorova; I. A. Chvala (Ветеринария сегодня)
Avian adenovirus was isolated from livers of 154-day-old hens on one farm located in the Krasnodar Krai in 2009. The virus was isolated in chicken Leghorn male hepatoma cell culture that exhibited cytopathogenic effect and identified as avian type С adenovirus by PCR followed by sequencing of hexon gene fragment. Hydropericardium syndrome developed in 7-day-old broiler chickens experimentally orally infected with the virus.